Perancangan User Interface Sistem Informasi Perpustakaan berbasis Web menggunakan Metode Human Centered Design (Studi Kasus: Perpustakaan SMKN 2 Blitar) - Hernindya Annisa Rahayu; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMKN 2 Blitar is a vocational school located in Blitar City. One of the existing facilities is the school library. The school library aims to support the activities of the school learning process. The library has activity functions including the management of book data, transaction data, member data, and report preparation. The function of these activities is still done manually so that an information system is needed to help the management process efficiently and effectively. Making a library information system does not only focus on content, but must consider user interface. The design of the user interface in this study uses the Human Centered Design (HCD) method to accommodate all the different needs of users. The Human Centered Design (HCD) method is a user-focused approach. Solution design user interface are evaluated using Heuristic Evaluation (HE) by the evaluator. This evaluation involves 2 types of evaluators, namely domain experts and system experts. The design of the user interface that was created resulted in 3 design views based on roles , namely library administrators, library users, and admins. The results of the evaluation of the user interface resulted in a total of 19 problems by the evaluator.